Gospel Selections: The First Book in Inuktitut Syllabics - Harper, Kenn (Études Inuit Studies)

(untitled) (Centre interuniversitaire d’études et de recherches autochtones (CIÉRA), 2022)
The syllabic writing system invented for the Cree was first introduced to Inuit in 1855 by Rev. Edwin A. Watkins (1827–1907) at Fort George and Little Whale River on the James Bay and Hudson Bay coasts, respectively. That same year at Fort George, Watkins prepared a small book of gospel selections in Inuktitut syllabics with the help of a young Inuk, Peter Okakterook (circa 1836–1858), and sent it to Rev. John Horden (1828–1893) in Moose Factory, who printed it on the press he had acquired for his mission. This small book is one of the earliest items printed on Horden’s press, and the only one printed in Inuktitut. Only one copy is known to have survived, at Library and Archives Canada, where it is catalogued under the title Selections from the Gospels in the Dialect of the Inuit of Little Whale River. The small volume of eight pages, transliterated into syllabics from Moravian publications prepared in the roman orthography used for Inuttut on the Labrador coast in present-day Nunatsiavut, was intended for use by Inuit in Nunavik. Although printed in syllabics using what are today seen as western Cree syllable-final symbols, the text is readable by and understandable to modern Inuit readers. This paper examines early missionary efforts to develop literacy for mission purposes among Inuit, including the printing and distribution of this small volume.